A possible activity cycle in Proxima Centauri - Cincunegui, Carolina Cecilia (2007)
Context.Several late-type stars present activity cycles resembling the Solar one. This fact has been observed mostly in stars ranging from F to K, i.e., in stars with a radiative core and an outer convective layer. Aims.This work aims at studying whether an activity cycle can be detected in the dM5.5e star Proxima Centauri, which is supposed to be completely convective. Methods.We present periodical medium-resolution echelle observations covering the complete visual range, which were taken at the CASLEO Argentinean Observatory. These observations are distributed over 7 years. We discarded the spectra that present flare activity, and analyze the remaining activity levels using four different statistical techniques to look for a period of activity. Results.We find strong evidence of a cyclic activity, with a period of ~442 days. We also estimate that the Ca S index varies around 130% due to activity variations outside of flares.